2005
DOI: 10.1121/1.1923369
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual compensation for effects of reverberation in speech identification

Abstract: Listeners were asked to identify modified recordings of the words "sir" and "stir," which were spoken by an adult male British-English speaker. Steps along a continuum between the words were obtained by a pointwise interpolation of their temporal-envelopes. These test words were embedded in a longer "context" utterance, and played with different amounts of reverberation. Increasing only the test-word's reverberation shifts the listener's category boundary so that more "sir"-identifications are made. This effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 23 publications
6
80
3
Order By: Relevance
“…Such enhancement is consistent with recent neural data that demonstrate the presence of reverberation-resistant coding of AM in the response properties of single neurons in the inferior colliculus (Delgutte et al, 2012;Kuwada et al, 2012). Because other studies have demonstrated that speech understanding in reverberant soundfields may be modified (Watkins, 2005) or improved (Brandewie and Zahorik, 2010;Srinivasan and Zahorik, 2013) with prior listening exposure to reverberation, and that this effect appears to most strongly influence the processing of the amplitude envelope of the speech signal (Watkins et al, 2011), it is important to determine whether AM sensitivity could be similarly affected by prior listening exposure to reverberation. This is the goal of the present study.…”
Section: Introductionsupporting
confidence: 78%
“…Such enhancement is consistent with recent neural data that demonstrate the presence of reverberation-resistant coding of AM in the response properties of single neurons in the inferior colliculus (Delgutte et al, 2012;Kuwada et al, 2012). Because other studies have demonstrated that speech understanding in reverberant soundfields may be modified (Watkins, 2005) or improved (Brandewie and Zahorik, 2010;Srinivasan and Zahorik, 2013) with prior listening exposure to reverberation, and that this effect appears to most strongly influence the processing of the amplitude envelope of the speech signal (Watkins et al, 2011), it is important to determine whether AM sensitivity could be similarly affected by prior listening exposure to reverberation. This is the goal of the present study.…”
Section: Introductionsupporting
confidence: 78%
“…The influence of reverberation on the identification of the stop-consonant ͓t͔ was assessed using a continuum of 11 words, changing in steps from plain "sir" ͑step 0͒ to plain "stir" ͑step 10͒. The words were generated by calculating the envelopes of "sir" and "stir" and imposing different ratios of these envelopes on the waveform of "sir" ͑refer to Watkins, 2005c, for details͒. The test-words of the continuum were perceived as "sir" at low step numbers and as "stir" at high step numbers.…”
Section: A Experimental Proceduresmentioning
confidence: 99%
“…Watkins also characterized the effect as extrinsic because it depends on information about the reverberation from surrounding speech and not the word itself. In his studies, Watkins investigated how the proposed compensation mechanism may pick up reverberation information from the context in order to increase speech intelligibility ͑e.g., Watkins, 2005cWatkins, , 2005bMakin, 2007a, 2007b͒. The "tails" that reverberation adds to the offsets of sounds seem to be particularly important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, provided the delay between two or more successive similar or identical sounds is sufficiently brief, a single sound is perceived near the location cued by the leading sound (Wallach et al 1949). In addition to providing for accurate sound source localization, the PE is thought to aid sound identification in reverberant environments, including (in humans) speech intelligibility (e.g., Brandewie and Zahorik 2010;Watkins 2005). The PE is a thus a key facility of normal hearing.…”
mentioning
confidence: 99%